Finding friends online: online activities by deaf students and their well-being. - Helen Blom (Public Library of Science (PLoS), 2014)
Generally, deaf and hard of hearing (D/HH) children have fewer friends than hearing peers and their friendships are of a lower quality. The research hypothesis was that using the computer to communicate with new online friends through social network sites or playing games with offline friends is associated with D/HH friendship qualities, because it removes certain communication barriers D/HH face in offline communication settings. With online questionnaires the relation between computer use and online, mixed (offline friend who you also speak in online settings), and offline friendship quality of D/HH and hearing students (18-25 years) was compared in both the Netherlands (n = 100) and the United States (n = 122). In addition, the study examined whether the different friendship qualities were related to the participants' well-being. Results showed that, in general, D/HH students' friendship qualities and levels of well-being were similar to their hearing peers. The quality of the mixed friendships was positively related to well-being. Furthermore, the frequency of pc use with both online and offline friends was positively related to friendships qualities in both hearing and D/HH students. A combination of the online and offline friendship seems to be the most important friendship type for both hearing and D/HH students and it is worthwhile to encourage this friendship type.